Predictors of Suboptimal Coronary Blood Flow during Primary Percutaneous Intervention - Asad Khan, Abdul Latif, Samiullah, Muhammad Shahab Uddin Khalil, Muzdalfa Parvez, Zarmina Ikram (Pakistan Journal of Medical & Health Sciences, 2022)
Background and aim: Suboptimal coronary blood flow following first percutaneous coronary intervention (PCI) is a multivariate phenomenon with several causes. Despite substantial research, recognized modifiable risk factors and an effective management plan are lacking. The present study intended to determine the several causes of suboptimal coronary blood flow during primary percutaneous intervention. Patients and Method: A retrospective study was carried out on 486 STEMI patients in the Interventional Cardiology Department, MTI-Hayatabad Medical Complex, Peshawar from June 2021 to May 2022. Patients (age>20 years) presented with initial percutaneous coronary intervention within 12 hours after onset of symptoms were enrolled. Patients’ physical examination, medical history, different risk factors, vital signs assessment, echocardiography, Killip class, laboratory investigation, and post-procedural ECG were recorded along with PCI data and associated catheterization. Clinical outcomes included MACE, ischemia-driven target vessel revascularization, reinfection, cardiac mortality, and post-catheterization were recorded. Descriptive statistics was done in SPSS version 26. Results: Of the total 486 STEMI patients, there were 412 (84.8%) male and 74 (15.2%) females. The overall mean age was 52.62± 8.64 years. The incidence of suboptimal flow (TIMI flow ≤2) and optimal flow (TIMI-3 flow) were 112 (23%) and 374 (77%) respectively. Age [OR 1.041/year: p<0.001], total stent length [OR 1.019 per 1 mm], low SBP [OR 1.021 per mm Hg], thrombus burden grade [OR 1.78], and baseline TIMI flow (≤1) [OR 1.72; p=0.021] were suboptimal flow independent predictors. Cardiac mortality and MACE were significantly higher after 30-days in suboptimal flow as compared to optimal flow. The prevalence of in-hospital mortality in suboptimal flow and optimal flow was 9.1% and 2.1% respectively. Conclusion: The present study found that suboptimal coronary flow after first PCI is substantially associated with higher in-hospital and cardiovascular mortality in STEMI. The most significant predictor of poor coronary flow is predilatation prior to stenting. Keywords: Suboptimal coronary flow, Primary percutaneous intervention, Predictors